2019
DOI: 10.1097/sap.0000000000002119
|View full text |Cite
|
Sign up to set email alerts
|

Chest Wall Masculinization in Female-to-Male Transsexuals

Abstract: Esthetic masculinization of the chest wall is one of the first surgical steps in female-to-male transsexual (FTMTS) reassignment. This surgical procedure is not a simple mastectomy: it is required for removal of breast tissue with glandular resection and skin excess revision, to reduce and replace the nipple-areola complex in the right location, minimizing chest wall scars. The creation of an esthetically pleasing male chest allows the patient to live at ease in the male gender role. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In our cohort, all transgender men perceived surgical interventions of GAS (genital and/or chest surgery) as very important for their wellbeing, with positive subjective changes in different areas of their life with no differences between the two groups. Although many authors have underlined the importance of chest surgery for transmen, these data suggest that HBSO is also important and has an impact on the life of trans men [ 17 , 22 ]. Confirming this, 54 to 63% of the transmen in our groups reported both interventions to be equally important.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our cohort, all transgender men perceived surgical interventions of GAS (genital and/or chest surgery) as very important for their wellbeing, with positive subjective changes in different areas of their life with no differences between the two groups. Although many authors have underlined the importance of chest surgery for transmen, these data suggest that HBSO is also important and has an impact on the life of trans men [ 17 , 22 ]. Confirming this, 54 to 63% of the transmen in our groups reported both interventions to be equally important.…”
Section: Discussionmentioning
confidence: 99%
“…The mean hospital stay length for combined surgery was 4.4 days with 2.7 days for HBSO alone, in line with the hospital stay for this type of surgery [ 27 , 28 ]. Data obtained from similar studies have indicated mean hospitalization stay ranging from zero to eight days [ 8 , 9 , 17 , 20 ]. Cizek et al recently highlighted the possibility of discharge on the same day of surgery and therefore the feasibility of the combined surgery of HBSO and bilateral mastectomy as day surgery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast amputation with a free nipple areolar complex graft is recommended for ptotic breasts [23]. A careful preoperative examination will identify these factors and will help the surgeon decide on the most appropriate technique for an individual [24].…”
Section: Chest Surgerymentioning
confidence: 99%